Deformation in a crustal scale shear zone: Errabiddy Shear Zone, Western Australia - Occhipinti, Sandra; Reddy, Steven (Geological Society of London, 2004)
Detailed mapping of four areas representing different geological units with varying formation histories within the crustal-scale Errabiddy Shear Zone shows an apparently simple temporal progression from foliation and mineral lineation development to folding nd then to brittle deformation across the shear zone. However, in detail the structural evolution of the shear zone shows considerable complexity. The dominant foliation throughout the shear zone was formed in the upper greenschist to amphibolite facies during the 2000 1960 Ma Glenburgh Orogeny, which involved the accretion of the Archaean to Palaeoproterozoic Glenburgh Terrane onto the Archaean Yilgarn Craton and the subsequent formation of the Errabiddy Shear Zone.Orthorhombic kinematic indicators formed during the Glenburgh Orogeny as did the widespread mineral lineation. These fabrics were overprinted by a greenschist facies deformation and metamorphic event during the 1830 1780 Ma Capricorn Orogeny.During the Capricorn Orogeny mineral lineation development was rare, and mostly took place in high-Capricorn strain zones in areas where a pre-existing Glenburghaged mineral lineation was present. Such mineral lineations trend parallel to Capricorn-aged fold hinges. Regardless of the presence or absence of Capricorn-aged mineral lineations, dextral strike-slip kinematics and simple shear indicated by delta and sigma porphyroclasts, and displacement along detachment faults, are prevalent close to discrete shear zone boundaries,within the Errabiddy Shear Zone. However, between shear zone boundaries flattening and pure shear dominated during the Capricorn Orogeny. This difference in Capricorn Orogeny kinematics throughout the shear zone is caused by strain partitioning -- although progressive deformation throughout the shear zone with dextral strike-slip faults overprinting older structures formed by pure shear also took place. These results suggest that analyses of small parts of shear zones may not give the complete history of an evolving transpressional shear zone because of the presence of strain partitioning and strain localization over time.